Protecting the Rights of Air Passengers in West Africa - (:unkn) unknown (My University, 2020)
While it is undeniable that air transport in Africa presents a rather disappointing image today, its future seems promising with the various initiatives taken here and there by States and, above all, by the AfricanUnion within the framework of the Single Market for Air Transport in Africa (MUTAA). However, it would be utopian to want a significant development of air traffic on the continent, if we continue to disregard the interests of African air passengers. Therefore, theissue of protecting the interests of African consumers of air transport services is of crucial importance. Theinterest of this study is therefore to draw the attention of the aviation authorities, and especially the airlines, to the need to ensure effective protection of African consumers and to improve the customer experience,which are important parameters for a competitive air transport service
Keywords: African Research